THE EFFECTIVENESS OF THE SYSTEM FOR ASSESSING THE FUNCTIONAL LITERACY OF STUDENTS IN COMPUTER SCIENCE BASED ON THE CRITERION APPROACH - Sagimbayeva, А.Е.; Avdarsol, С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In the article, based on the criterion approach, the effectiveness of the system for assessing the functional literacy of students in computer science is proved by conducting a pedagogical experiment and conclusions are drawn about the results of practical work. The teaching experience consists of three stages. At the ascertaining stage, it was revealed to what extent the assessment tasks in computer science were compiled taking into account the directions of functional literacy of students. At the applicant stage, tasks and tasks were developed to assess the functional literacy of students based on a criteria-based approach in computer science. At the educational and control stage, the influence of the functional literacy assessment system, developed on the basis of a criterion approach in computer science, on the quality of knowledge and the methodology of teaching students in computer science was revealed. In addition, during the practice, the educational and methodological manual "tasks for assessing the functional literacy of students in computer science" was used. During the training in the control groups, the assessment of knowledge was carried out according to the traditional method, and in the experimental groups on tasks to assess the functional literacy of students based on the criteria approach.